Founders of the RAS: Daniel Moore. Issue 5 (1st October 2018) - Edmunds, Michael
Abstract : The successful lawyer and benefactor was involved with many scientific societies, recounts Mike Edmunds. Abstract : Moore was a successful lawyer and generous benefactor involved with many scientific societies, recounts Mike Edmunds, despite leaving no evidence of scientific work of his own.